Osteoprotegerin reduces the development of pain behaviour and joint pathology in a model of osteoarthritis. Issue 8 (30th May 2013) - Sagar, Devi Rani; Ashraf, Sadaf; Xu, Luting; Burston, James J; Menhinick, Matthew R; Poulter, Caroline L; Bennett, Andrew J; Walsh, David A; Chapman, Victoria
Abstract : Background: Increased subchondral bone turnover may contribute to pain in osteoarthritis (OA). Objectives: To investigate the analgesic potential of a modified version of osteoprotegerin (osteoprotegerin-Fc (OPG-Fc)) in the monosodium iodoacetate (MIA) model of OA pain. Methods: Male Sprague Dawley rats (140–260 g) were treated with either OPG-Fc (3 mg/kg, subcutaneously) or vehicle (phosphate-buffered saline) between days 1 and 27 (pre-emptive treatment) or days 21 and 27 (therapeutic treatment) after an intra-articular injection of MIA (1 mg/50 µl) or saline. A separate cohort of rats received the bisphosphonate zoledronate (100 µg/kg, subcutaneously) between days 1 and 25 post-MIA injection. Incapacitance testing and von Frey (1–15 g) hind paw withdrawal thresholds were used to assess pain behaviour. At the end of the study, rats were killed and the knee joints and spinal cord removed for analysis. Immunohistochemical studies using Iba-1 and GFAP quantified levels of activation of spinal microglia and astrocytes, respectively. Joint sections were stained with haematoxylin and eosin or Safranin-O fast green and scored for matrix proteoglycan and overall joint morphology. The numbers of tartrate-resistant acid phosphatase-positive osteoclasts were quantified. N=10 rats/group. Results: Pre-emptive treatment with OPG-Fc significantly attenuated the development of MIA-induced changes in weightbearing, but not allodynia. OPG-Fc decreased osteoclast number, inhibited the formation of osteophytes and improved structural pathology within the joint similarly to the decrease seen after pretreatment with the bisphosphonate, zoledronate. Therapeutic treatment with OPG-Fc decreased pain behaviour, but did not improve pathology in rats with established joint damage. Conclusions: Our data suggest that early targeting of osteoclasts may reduce pain associated with OA.